Retraction notice to “Novel targets and improved immunotherapeutic techniques with an emphasis on antimycosal drug resistance for the treatment and management of mycosis” [Heliyon 10 (2024) e35835] - Riya Sarkar; Krishnendu Adhikary; Arundhati Banerjee; Krishnendu Ganguly; Riya Sarkar; Satyajit Mohanty; Rumpa Dhua; Koushik Bhattacharya; Deepika Ahuja; Suchandra Pal; Rajkumar Maiti (Heliyon)
This article has been retracted: please see Elsevier policy on article withdrawal (https://www.elsevier.com/about/policies-and-standards/article-withdrawal).This article has been retracted at the request of the Editor-in-Chief.An investigation conducted on behalf of the journal by Elsevier's Research Integrity & Publishing Ethics team found phrases that make some passages in the article difficult to parse. The authors were requested to explain the use of these passages of text but were unable to do so. The Editor has lost confidence in the findings of the article and has determined that it should be retracted.The authors disagree with this retraction and dispute the grounds for it.